Building Response Strategies to Climate Change in Agricultural Systems in Latin America - World Bank (Washington, DC, 2013)
This report, Building Response Strategies to Climate Change in Agricultural Systems in Latin America, reports the results of action research to identify and prioritize stakeholder driven, locally relevant response options to climate change in Latin American agriculture. The study has three primary objectives. The first is to develop and apply a pilot methodology for assessing agricultural vulnerability to climate change and for formulating adaptation response strategies to inform private and public sector decisions in the Latin America region. The study is principally concerned with adaptation responses to climate change, rather than mitigation. The second objective is to formulate recommendations for investments in each of the selected agro-ecosystems in a range of areas including agricultural technology adaptation, infrastructure investments, public and private sector support activities, and institutional and policy changes. The final objective is to disseminate the study results in the Latin America region and other parts of the world to help increase understanding of the impacts of climate change and alternative adaptation response strategies. This methodology can be used by the Bank to support client countries in defining response strategies, designing related investment projects, and formulating policy changes.